Does Money Talk? Divestitures and Corporate Environmental and Social Policies. (9th May 2022) - Gantchev, Nickolay; Giannetti, Mariassunta; Li, Rachel
Abstract: Can shareholders' divestitures and threats of exit trigger improvements in firms' environmental and social (E&S) policies? We show that E&S incidents are followed by some, but relatively small, divestitures. Nevertheless, following E&S incidents, firms with a one-standard-deviation higher E&S-conscious institutional ownership decrease their greenhouse gas emissions by 36.5% and improve their E&S scores by 7.2% more than other firms if their managers receive equity compensation. We do not observe any improvements associated with sales in E&S-conscious countries. Our results suggest that the threats of future exits and divestitures can improve E&S policies if shareholders are E&S-conscious and managers' compensation is linked to the stock price.